Automating DevOps with GitLab CI/CD pipelines : build powerful CI/CD pipelines to verify, secure, and deploy your code using real-life examples /: build powerful CI/CD pipelines to verify, secure, and deploy your code using real-life examples. (2023) - Cowell, Christopher; Lotz, Nicholas; Timberlake, Chris
No abstract available